2018
DOI: 10.1097/pas.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

Age and CD20 Expression Are Significant Prognostic Factors in Human Herpes Virus-8-negative Effusion-based Lymphoma

Abstract: Human herpes virus-8 (HHV-8)-negative effusion-based lymphoma (HHV-8-negative EBL) can be distinguished from primary effusion lymphoma based on clinical and pathologic findings. Although the morphology between the 2 is similar and they both originate from body cavities with serous effusions and are characterized by lack of tumor masses, HHV-8-negative EBL generally occurs in older patients, and has favorable response to therapy and better prognosis than primary effusion lymphoma. However, no systematic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Moreover, CD20 expression is a biomarker for better overall survival in HHV8-negative EBL patients. 17 In the case of our patient, CD20 positivity provided us with a targetable and less toxic treatment option in comparison to standard chemotherapy. Furthermore, immunostaining for HHV8 and plasma cell marker CD138 were both negative, eliminating a possible PEL diagnosis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, CD20 expression is a biomarker for better overall survival in HHV8-negative EBL patients. 17 In the case of our patient, CD20 positivity provided us with a targetable and less toxic treatment option in comparison to standard chemotherapy. Furthermore, immunostaining for HHV8 and plasma cell marker CD138 were both negative, eliminating a possible PEL diagnosis.…”
Section: Discussionmentioning
confidence: 64%
“…As such, CD20‐targeted therapy using monoclonal antibodies such as rituximab can be employed in most cases of HHV8‐negative EBL. Moreover, CD20 expression is a biomarker for better overall survival in HHV8‐negative EBL patients 17 …”
Section: Discussionmentioning
confidence: 99%
“…In the case of PEBL, it has been further reported that increased age and CD20 positivity appear to be favorable independent prognostic factors, both of which were present in our patient. 10 For this reason, and as we and others have suggested elsewhere, CD20 targeting therapy with rituximab in combination with thoracentesis of effusion fluid seems to be an acceptable alternative treatment option in CD20 positive patients who cannot withstand CHOP-like chemotherapy due to increased age or an inadequate performance functional status. 11 , 14 , 18 Our patient was able to successfully complete R-CHOP after initial treatment with rituximab monotherapy and rituximab-cyclophosphamide.…”
Section: Discussionmentioning
confidence: 85%
“…Cases of HHV8‐negative primary lymphomatous effusions have been reported and these are referred to collectively as primary HHV8‐unrelated effusion large B‐cell lymphoma, primary HHV8‐negative effusion‐based lymphoma, or HHV8‐unrelated PEL‐like lymphoma. Intriguingly, patients of East Asian origin—especially Japanese—account for approximately 60% of cases of reported HHV8‐unrelated effusion large B‐cell lymphomas 6‐13 . HHV8‐unrelated effusion large B‐cell lymphoma is often seen in individuals with underlying adverse medical conditions, such as liver cirrhosis and congestive heart failure, which lead to fluid overload in body cavities 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…HHV8‐unrelated effusion large B‐cell lymphoma is often seen in individuals with underlying adverse medical conditions, such as liver cirrhosis and congestive heart failure, which lead to fluid overload in body cavities 7,8 . HHV8‐unrelated effusion large B‐cell lymphoma exhibits an overlapping clinical presentation with PEL, but with a distinct immunophenotype (usually positive for B‐cell‐associated antigens) and lack of association with HIV 6‐10 . Clinical outcomes of cases of HHV8‐unrelated effusion large B‐cell lymphoma are relatively favorable compared with cases of PEL, although some have an aggressive clinical course with poor prognosis 6,11‐13 .…”
Section: Introductionmentioning
confidence: 99%